Mapping chromosomal regions controlling resistance to gastro-intestinal worms in mice. Poster presentation - Iraqi, F.A.; Menge, D.; Gibson, P.J.; Baker, R.L.; Wakelin, D.; Behnke, J.M.; Lowe, A.; Teale, A.J. (IMGS, 2001)
Breeds of cattle, sheep and goats have been identified which are genetically resistant and/or tolerant to gastro-intestinal nematode parasites. Mapping and cloning of resistant genes will facilitate Development of new breeds of livestock, which combine this important disease resistance trait with desirable productivity traits. A genome-wide scan approach has been used in a mouse model for mapping genes that are resistant to nematode parasites. A F2 population, derived from a cross between resistant SWR and susceptible CBA inbred mouse strains, was phenotyped for resistance to the effects of Heligmosomoides polygyrus infection. Microsatellite markers were genotyped on mice representing phenotypic extremes (i.e resistant and susceptible) for worm counts after a 6-week trickle infection period. Genetic and phenotypic data were analysed with MapMaker/Exp/QTL and least squares regression analysis programmes. The location of the QTL effect and the size of this affect were very similar in the two sets of analyses. This study has identified four chromosomal regions with significant effects on resistance to nematode infection in the F2 mice. The largest effect was found on chromosome 1 with a LOD score of 7.9. Three additional significant effects were found on chromosomes 11, 12 and 17 with LOD scores of 3.4, 2.1 and 3.2, respectively. A number of candidate genes for nematode infection resistance can be identified based on the QTL locations. Currently an F6 population is being produced to allow higher resolution mapping preparatory to positional cloning, which may lead to identification of the homologous genes in domestic ruminants through comparative mapping.